Vocal Disturbances Encountered Among Voice-Related Professionals - Shaboyan, Mery
This article aims to explore the adverse factors associated with voice-related professions and their impact on the vocal apparatus, offering an in-depth analysis of underlying causes, consequences, and symptomatic manifestations. The article thoroughly examines the primary causes of voice disorders frequently encountered by voice-related professionals and discusses specific physical illnesses that may be incompatible with continued professional voice use. A desk review methodology has been employed in this study. This article provides a comprehensive exploration of the vocal challenges faced by professionals in voice-intensive occupations, emphasizing the importance of vocal preservation and effective preventive practices. It underscores that voice quality significantly influences professional performance across diverse fields including teaching, acting, singing, broadcasting, interpreting, and commanding roles within the military and judiciary. The study identifies several primary factors contributing to vocal impairments, notably excessive vocal load, incorrect vocal techniques, chronic stress, poor environmental conditions, and detrimental lifestyle habits. Prevention strategies are systematically categorized into primary, secondary, and tertiary levels, emphasizing early identification, intervention, and rehabilitation for sustained vocal health. Ultimately, the article argues for greater awareness and education on vocal hygiene and advocates the implementation of targeted preventive measures. Maintaining voice quality is presented not merely as a professional necessity but as a critical component for overall health, professional effectiveness, career longevity, and enhanced quality of life among voice professionals.
Keywords: Vocal professionals